Key performance indicators to characterize the evolution of the future electricity system - Hellman, Cassandra; Elofsson, David (My University, 2017)
The electricity system is facing extensive challenges in the coming years transitioning towards a low-carbon economy by 2050. Understanding the characteristics of this transition can play a key part in facilitating its implementation. This thesis investigates using Key Performance Indicators (KPIs) to characterize the evolving electricity system and to visualize the system’s progress towards sustainability over time, a topic which is identified as a gap in the current literature. Three distinct policy scenarios for 2050 are analyzed using a set of eight KPIs developed in this study. These KPIs are conceived by a process of brainstorming and extraction through selection criteria. Furthermore, a method for visualizing sustainable development is conceived by aggregating KPIs into an index. This index represents multiple aspects of sustainable development and illustrates scenario progress towards sustainability over time. In addition, creating a matrix-representation of relative scenario acceptance provides a tool indicating challenges in policy implementation. The findings suggest that the KPIs and visualization method developed in this study can serve as a tool to understand and visualize the development of the electricity system as described by a techno-economic model. While individual KPIs gives limited representation of sustainability, the aggregation of several KPIs into one index contributes with a multifaceted perspective. Presented methods for visualizing sustainability do not provide a holistic representation of sustainable development but contributes to the research field with expedient tools.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering